Pagan Mysticism and Gaucho Teratology (2017)
This work proposes a reading of Aballay (1978) by Antonio di Benedetto. The starting point of this reflection is the problem of the gaucho tradition this work interrogates. In this context, critical readings that interpet Aballay from a moralist or religious rereading of gauchesca literature are confronted. On the contrary, a hypothesis is proposed about the mysticism of the protagonist, interpreting his adventures as a sacred experience.